2020
DOI: 10.1038/s41392-020-00323-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in targeted therapy for esophageal cancer

Abstract: Esophageal cancer (EC) is one of the most lethal cancers in the world, and its morbidity and mortality rates rank among the top ten in China. Currently, surgical resection, radiotherapy and chemotherapy are the primary clinical treatments for esophageal cancer. However, outcomes are still unsatisfactory due to the limited efficacy and severe adverse effects of conventional treatments. As a new type of approach, targeted therapies have been confirmed to play an important role in the treatment of esophageal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
246
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(291 citation statements)
references
References 115 publications
0
246
0
Order By: Relevance
“…The 5-year overall survival (OS) of advanced ESCC is only 18.8%. 3 , 4 Unfortunately, most patients have advanced-stage diseases at first diagnosis, generally because of the absence of clinical symptoms. 5 Recently, multidisciplinary therapy methods, including surgical resection, radiotherapy, chemotherapy, and targeted therapy, provide new options to prolong OS.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year overall survival (OS) of advanced ESCC is only 18.8%. 3 , 4 Unfortunately, most patients have advanced-stage diseases at first diagnosis, generally because of the absence of clinical symptoms. 5 Recently, multidisciplinary therapy methods, including surgical resection, radiotherapy, chemotherapy, and targeted therapy, provide new options to prolong OS.…”
Section: Introductionmentioning
confidence: 99%
“…EC can be histologically classified as esophageal squamous cell carcinoma (ESCC) or esophageal adenocarcinoma (EAC), which has distinct pathogenesis, molecular characteristics, and geographical distribution ( Cancer Genome et al, 2017 ; Lagergren et al, 2017 ). Clinically, chemotherapy has been one of the major therapeutic approaches in the trimodality therapy of EC; molecular targeted therapy and immune checkpoint inhibitors have been evaluating in preclinical and clinical trials ( van Hagen et al, 2012 ; Smyth et al, 2017 , 2021 ; Yang et al, 2020 ). However, despite recent advances in multidisciplinary management, the treatment of EC is still a relentless challenge partly owing to the fact that numerous patients are intrinsically insensitive or adaptively resistant to therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Nowdays, it has been reported that a variety of biomarkers can affect the prognosis of patients with esophageal cancer by changing the immune microenvironment of the tumor, such as MiR-201, MiR-503 and PD-L1 [19][20][21] . PD-L1 has been proved to be the target of immunotherapy for patients with ESCC [22] . In this study, we analyzed the survival correlation of 223 DEGs.…”
Section: Discussionmentioning
confidence: 99%